COVID-19 and Science: The value of knowledge in times of pandemic (Research, Society and Development, 2021)
Coronavirus disease 2019 (COVID-19) has become a global pandemic and, since its first identification, evoked in the heads of states and the general population faster responses to cope with it. Faced with this global pandemic scenario, science (re)emerged as an important support tool, achieving greater visibility and projection in society. Considering the importance of science to produce systematic and reliable knowledge, this study proposes to present observations in the form of a theoretical-reflective essay constructed by analyzing the literature published in books and scientific articles about the role of science in the context of COVID-19, in view of scientific practice, the paths technological advances, obstacles, possible paths and their relationship with the formation of citizenship in society. In view of so many studies published in the literature, it is important to discuss and mature scientific findings through a critical-reflexive analysis by individuals within a group capable of making a well-founded judgment. In addition, the promotion of education and scientific literacy are essential in the development of society's autonomy and criticality. Otherwise, misinterpretations and pseudoscience fallacies may negatively effects on governance, health management and society, suggesting inconsistent public policies and putting the population's health at risk.